EPEN-11. Phase 0/I Study of GM-CSF and Intrathecal Trastuzumab In Children With Recurrent Posterior Fossa Ependymoma. (3rd June 2022) - Norris, Gregory; Widener, Melissa; Amani, Vladamir; Donson, Andrew; Schissel, Debra; Bruno, Courtney; Mettetal, Ashley; Ramirez, Dominique; Gustafson, Daniel; Hankinson, Todd; Handler, Michael; Macy, Margaret; et al.
Abstract: BACKGROUND: Posterior fossa ependymoma (PF EPN) is a pediatric central nervous system malignancy that has a poor outcome to standard therapeutic approaches. The majority of PF EPN have been shown to harbor increased HER2 expression, making it a logical therapeutic target. Trastuzumab is a monoclonal antibody that targets HER2, and sargramostim (GM-CSF) stimulates hematopoietic progenitor cell proliferation. The combination of trastuzumab and GM-CSF has been shown to trigger antibody-dependent cell cytotoxicity in-vitro in patient-derived PF EPN cell lines. METHODS: Children aged 1–21 years with relapsed PF EPN, no ventriculoperitoneal shunt, and no CSF obstruction are eligible for the Phase 0/I single-institution clinical trial at Children's Hospital Colorado. Stratum 1 involves intrathecal (IT) trastuzumab and subcutaneous (subQ) GM-CSF prior to standard-of-care surgical resection. Stratum 2 involves a 3 + 3 phase I design with serial IT trastuzumab doses, each preceded by three days of GM-CSF, to establish the maximum tolerated dose for IT trastuzumab. RESULTS: Trastuzumab was detected in a sufficient number of tumors after presurgical IT delivery in Stratum 1 to open Stratum 2. Seven patients (3 female) have been enrolled in Stratum 2. Median age at enrollment is 8.1 years (range, 3–20 years). CSF pharmacokinetic analysis demonstrate detectable trastuzumab up to 14 days after IT doses. No dose-limiting toxicities or grade 3 or 4 adverse events have occurred. Four patients completed all planned study therapy and remain progression-free post-therapy (median, 23 months, range, 6-42 months). Three patients progressed on therapy (median, 4 cycles). Biologic correlative studies are in process. CONCLUSIONS: IT trastuzumab penetrates PF EPN tumor tissue and demonstrates an excellent safety profile. Stratum 2 remains open to accrual at Dose Level 2. IT trastuzumab+GM-CSF warrants consideration for a multi-institutional Phase II trial.